The potential to manage releases of Bacillus anthracis using bioretention and a high flow media filter: Results of simulated runoff testing with tracer spores Bacillus globigii - Boening-Ulman, Kathryn M.; Mikelonis, Anne M.; Heckman, J. Lee; Calfee, M. Worth; Ratliff, Katherine; Youn, Sungmin; Smith, Joseph S.; Mitchell, Caleb E.; Hunt, William F.; Winston, Ryan J. (Journal of environmental management, 2024)
The threat of bioterrorism has spurred research on the decontamination and containment of different agents. Anthrax [causative agent Bacillus anthracis (Ba)] is a disease that can lead to severe infections within human and animals, particularly when inhaled. This research investigated the use of spore-contaminated simulated runoff events into stormwater control measures (SCMs), which are designed to retain and improve the quality of runoff and may have the potential to filter and contain the spores. In this study, the effectiveness of a bioretention cell (BRC) and high flow media filter (HFMF) in Huron, Ohio, were evaluated for removal of Bacillus globigii (Bg) spores (a harmless cognate of Ba). Three 4–8 mm simulated runoff events were created for each SCM using a fire hydrant and Bg spores were injected into the runoff upstream of the SCM inlets. The BRC significantly (p < 0.001) outperformed the HFMF in reducing Bg concentrations and loads, with an average load reduction of 1.9 log (∼99% reduction) compared to 0.4 (∼60% reduction), respectively. A probable critical design factor leading to these differences was the infiltration rate of the media and subsequent retention time within the filters, which was supported by similar disparities in suspended solids reductions. Differences in spore removal may also have been due to particle size distribution of the HFMF, which was more gravelly than the bioretention cell. At 3 and 6 months after the-simulated runoff tests, soil samples taken from both SCMs, yielding detectable Bg spores within the top 15 cm of media, with increased spore concentrations where ponding occurred for longer durations during the tests. This suggests that forebays and areas near inlets may be hotspots for spore cleanup in a real-world bioterrorism incident. [Display omitted] •Bacillus anthracis releases may be partially contained by stormwater controls.•Removal of tracer spores tested within bioretention & high flow media filter.•In simulated runoff tests, media texture influenced spore removal rates.•Spore contamination levels maintained in SCM media 6 months after testing.•Stormwater control measures may be part of a series of decontamination efforts.